Feeling the Right Personality. Recruitment Consultants’ Affective Decision Making in Interviews With Employee Candidates - Kinnunen, Taina; Parviainen, Jaana (Nordic Journal of Working Life Studies, 2016)
The pressure to find the ‘right’ personalities to strengthen customer service and working teams has made staffing decisions critical for organizations. Therefore, recruitment is more often outsourced and done so on a global level. By analyzing interviews with recruitment consultants, this article explores how consultants work in order to find the recruitment candidates with the most potential for their clients. It discusses recruitment as a process of affective decision-making where consultants use their ‘gut feelings’, that is, their own embodied affects, to secure the optimal ‘organizationperson fit’. Different kinds of details in the candidate’s appearance and micro-movements of the body cause ‘good vibrations’ or ‘strange feelings’ in the consultant’s affective body, which guides the selection among the candidates. By deconstructing the concept of ‘affect’, the article develops an understanding of recruitment as a practice where the embodied histories of consultants themselves play a key role in recruitment. The article claims that, as a result of competition in the business, the recruitment consultant relies on stereotypical performances of the ideal worker.